Health-related quality of life of young people and adults with primary or recurrent episodes of genital herpes: a mixed methods systematic review protocol. (May 2018) - Bennett, Clare; Rebafka, Anne; Carrier, Judith; Edwards, Deborah; Jones, Jonathan
Abstract : Review question: The review questions are: What is it like to live with primary or recurrent episodes of genital herpes? What interventions improve the health-related quality of life (HRQOL) of young people and adults with primary or recurrent episodes of genital herpes? The specific objectives are: To identify and explore the perceptions and experiences of young people and adults with symptomatic primary or recurrent genital herpes regarding the impact of genital herpes on their HRQOL. To determine the effectiveness of interventions for improving the HRQOL of young people and adults with primary or recurrent genital herpes. This mixed methods review seeks to develop an aggregated synthesis of quantitative and qualitative data on the HRQOL implications of genital herpes for the individual in order to derive conclusions and recommendations for clinical practice and policy decision making.